Mallas en la reparación de la pared abdominal - Rappoport S., Jaime (Revista Hospital Clínico Universidad de Chile, 2007)
The modern concept about the aetiology of hernias, referred to deficiencies in the metabolism of the collagen, makes recommendable the use of a prosthetic material in the hernia repair. The material most widely spread is the polypropylene monofilament, macroporous, sheet with the exception of the intraperitoneal use. The long term follow - up of the patients and his results, allow us, to evaluate theresults of a specific material.